TRIZ application in semiconductor manufacturing & case studies - Yeoh, Tay-Jin; Yeoh, Teong-San; Song, Chia-Li (Universiti Malaysia Perlis (UniMAP), 2010)
TRIZ is a structured methodology for modeling problems, tools for the models and nally models of solutions. TRIZ is a recognized international science of creativity, based on the laws of physics and innovative patents distilled to numerous problem solving tools. It is a toolbox with 12 tools which provides methods to create breakthrough ideas. Three TRIZ tools, Contradiction, 40 Inventive Principles, and Process Analysis are described.